2000
DOI: 10.1007/pl00008892
|View full text |Cite
|
Sign up to set email alerts
|

Communication between plants: induced resistance in wild tobacco plants following clipping of neighboring sagebrush

Abstract: The possibility of communication between plants was proposed nearly 20 years ago, although previous demonstrations have suffered from methodological problems and have not been widely accepted. Here we report the first rigorous, experimental evidence demonstrating that undamaged plants respond to cues released by neighbors to induce higher levels of resistance against herbivores in nature. Sagebrush plants that were clipped in the field released a pulse of an epimer of methyl jasmonate that has been shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
273
3
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(296 citation statements)
references
References 27 publications
8
273
3
12
Order By: Relevance
“…Volatile chemicals might also affect self-discrimination in C. japonica tendrils. Volatile compounds play an important role in inter-plant interactions [41][42][43]. Volatile cues from genetically identical sagebrush Artemisia tridentata cuttings induce resistance to herbivores more efficiently than cues from non-self cuttings [15].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile chemicals might also affect self-discrimination in C. japonica tendrils. Volatile compounds play an important role in inter-plant interactions [41][42][43]. Volatile cues from genetically identical sagebrush Artemisia tridentata cuttings induce resistance to herbivores more efficiently than cues from non-self cuttings [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that plant behavior is simpler than that of animals. Now, however, plant biologists have discovered that experiential accumulation through conditioning can also significantly affect plant behavior [12,23,24]. Plants also have memory and communication behavior, even if they lack a central nervous system.…”
Section: Root System Coevolutionmentioning
confidence: 99%
“…Changes in water or nutrient availability or presence of obstacles are perceived belowground by roots (Smith, 2000;Hodge, 2004). Additionally, competing neighbor plants can be directly perceived both above-and belowground through touch perception (de Wit et al, 2012) or volatile cues from neighboring plants (Karban et al, 2000). These chemical cues can also inform the plant about the metapopulation of microbes in the surrounding rhizosphere.…”
Section: Introductionmentioning
confidence: 99%